Homework Help

Inverse function.Prove that f(x)=x^3+x has inverse function.  

user profile pic

greynose | Student, Undergraduate | (Level 2) Honors

Posted May 3, 2011 at 12:28 AM via web

dislike 0 like
Inverse function.

Prove that f(x)=x^3+x has inverse function.

 

2 Answers | Add Yours

user profile pic

giorgiana1976 | College Teacher | (Level 3) Valedictorian

Posted May 3, 2011 at 10:23 AM (Answer #2)

dislike 0 like

For the given function to have an inverse function f^-1(x), it has to be bijective.

For the function to be bijective, it has to be one to one function and on-to function.

We'll prove that the given function is one to one function.

For this reason, we'll have to prove that the function is strictly increasing or decreasing. For this reason, we'll determine the first derivative of the function.

f'(x) = (x^3+x)'

f'(x) = 3x^2 + 1

It is obvious that f'(x)>0 for any value of x, so the function f(x) is an one to one function.

Let's prove that the function is an on to function. We'll determine the limits of the function for x-> +infinite and x->-infinite

Lim f(x) = lim (x^3 + x) = (+infinite)^3 + infinite = +infinite

Lim f(x) = lim (x^3 + x) = (-infinite)^3 - infinite = -infinite

So, f(x) is a continuous function, then it is an on-to function.

Since the fuction is both, one to one and on to function, it is bijective and it does exist f^-1(x).

user profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted March 6, 2013 at 2:19 PM (Answer #3)

dislike 0 like

You should notice that the function `f(x) = x^3 + x` is continuous over `(-oo,oo)` , hence it is bijective.

You may evaluate its inverse `f^(-1)(x)` , using the following relation between a function and its inverse, such that:

`(f^(-1)(x))' = 1/(f'(x)) => (f^(-1)(x))' = 1/(3x^2 + 1)`

You need to integrate both sides to evaluate `f^(-1)(x)` such that:

`f^(-1)(x) = int 1/(3x^2 + 1) dx`

`f^(-1)(x) = (1/3) int 1/(x^2 + 1 / 3 ) dx`

`f^(-1)(x) = (1/3)*1/(1/sqrt3) tan^(-1) (x/(1/sqrt3)) + c`

`f^(-1)(x) = (sqrt3/3)tan^(-1)(x*sqrt 3) + c`

Hence, testing if there exists the inverse function, yields that there exists `f^(-1)(x) = (sqrt3/3)tan^(-1)(x*sqrt 3) + c.`

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes